2008
DOI: 10.1021/ac801114j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Multiple Cell Types in Parallel Microfluidic Channels: Monitoring Platelet Adhesion to an Endothelium in the Presence of an Anti-Adhesion Drug

Abstract: A simple method for immobilizing endothelial cells in the channels of a microfluidic device fabricated with soft lithography is presented that requires no surface oxidation of the substrate material used in conjunction with the microfluidic device and is operable even with a reversible seal. Specifically, optimal conditions for culturing bovine pulmonary artery endothelial cells (bPAECs) to the surface of a Petri dish were investigated. The parameters investigated included fibronectin concentration, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…It seems that almost all of these effects are beneficial. While previous studies have demonstrated that C-peptide affects intracellular mechanisms, its ability to stimulate ATP release from RBCs enables C-peptide to affect intercellular communication [59,60], and mechanisms. To date, our group has demonstrated that RBCderived ATP, stimulated by C-peptide, can increase NO production in endothelial cells and platelets, and affect platelet adhesion to endothelial cells.…”
Section: C-peptide: a Multi-tasking Molecule Or Stimulus Of Such?mentioning
confidence: 99%
“…It seems that almost all of these effects are beneficial. While previous studies have demonstrated that C-peptide affects intracellular mechanisms, its ability to stimulate ATP release from RBCs enables C-peptide to affect intercellular communication [59,60], and mechanisms. To date, our group has demonstrated that RBCderived ATP, stimulated by C-peptide, can increase NO production in endothelial cells and platelets, and affect platelet adhesion to endothelial cells.…”
Section: C-peptide: a Multi-tasking Molecule Or Stimulus Of Such?mentioning
confidence: 99%
“…Studies have shown good viability of living cells when grown on cellular microenvironmental chips [359][360][361][362][363][364][365][366][367][368][369][370]. Microfluidics replaces the parallel plate chambers for cell growth, and shear stress investigations establish the need to match the length scales between the fluidic channels and the cells [359][360][361][362][363][364][365][366][367][368][369][370].…”
Section: Biocompatibility and Cell Viability Within Microfluidic Systemsmentioning
confidence: 99%
“…Microfluidics replaces the parallel plate chambers for cell growth, and shear stress investigations establish the need to match the length scales between the fluidic channels and the cells [359][360][361][362][363][364][365][366][367][368][369][370].…”
Section: Biocompatibility and Cell Viability Within Microfluidic Systemsmentioning
confidence: 99%
“…For example, the binding of leukocytes to endothelial cells is an essential step in inflammation, 4 while the endothelium-mediated activation of blood platelets is important in clotting and thrombosis. 6 Multiple reports have been published by groups that studied the adhesion of leukocytes 156 or platelets 58,92,127 to endothelial cells or endothelial cell-derived adhesion factors in microfluidic devices. These reports show that microfluidic cell interaction studies require less sample and reagents than similar, conventional studies.…”
Section: Cell Interactionsmentioning
confidence: 99%
“…Moreover, a number of these studies already show increased throughput by using parallel channels in one device. 58,92,156 Three-dimensional culturing An important factor in vascular cell physiology is its three-dimensional microenvironment. Cells are embedded in an environment that comprises other cells, extracellular matrix proteins, bodily fluids and blood.…”
Section: Cell Interactionsmentioning
confidence: 99%